2020
DOI: 10.4055/cios.2020.12.1.55
|View full text |Cite
|
Sign up to set email alerts
|

Review of Physician Referrals to Orthopedic Spine versus Neurosurgery

Abstract: Spinal disorders continue to affect millions of patients a year, causing pain and disability that permanently alter their daily life. First described by Hippocrates and the Greek, these conditions are found in an increasing number of patients complaining of neck and back pain each year, costing patients and our health care system millions of dollars in treatment a year. [1][2][3][4][5][6] Primary care, emergency medicine, and pain physicians are usually the first health care providers that see these patients a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 23 publications
0
3
0
2
Order By: Relevance
“…The scoping review had shown that complications for the two specialties are not statistically different. [1][2][3][4][5][6][7][8][9][10] However, there is still some variations in the complications between specialties (e.g., blood transfusions and dural tear). 3 These complications may reflect the differences in technique and case exposure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The scoping review had shown that complications for the two specialties are not statistically different. [1][2][3][4][5][6][7][8][9][10] However, there is still some variations in the complications between specialties (e.g., blood transfusions and dural tear). 3 These complications may reflect the differences in technique and case exposure.…”
Section: Discussionmentioning
confidence: 99%
“…In general, spine surgeries are performed by either of the two specialties: neurosurgery and orthopedics. [1][2][3][4][5][6][7][8][9][10] Despite the inherent differences in training pathway, there exists a significant overlap in the patient population and management by both specialties. 1 To date, several studies have attempted to compare spine surgeries between the two specialties.…”
Section: Introductionmentioning
confidence: 99%
“…Los médicos de primer contacto tienen ciertos sesgos y patrones cuando se trata de referir un paciente con patología de columna vertebral con el especialista (falta de conocimiento o interés); estos sesgos y patrones pueden ser secundarios a experiencias personales con los cirujanos de columna con los que se han relacionado (falta de profesionalismo, rivalidad, egocentrismo, malas relaciones interpersonales), el acceso limitado a este tipo de especialistas, las campañas de marketing (la lumbalgia, al ser la segunda causa de consulta ortopédica, existe mucho marketing de manejos «alternativos»), las iniciativas o políticas del hospital donde laboren (patología de columna cervical sólo es atendida por neurocirujanos y patología de columna lumbar por ortopedistas), así como muchos otros factores. 7 La comunicación abierta, la educación acerca de capacidades y alcances del urgenciólogo, así como mejores relaciones entre los cirujanos de columna y los médicos de primer contacto podría ayudar a tener una adecuada referencia con el especialista en columna y ayudar a los pacientes independientemente de la patología. 7 La mayoría de los médicos de atención primaria se sienten «algo» preparados al comunicar el riesgo, así como para identificar los posibles casos de emergencia de la columna vertebral.…”
Section: Discussionunclassified
“…7 La comunicación abierta, la educación acerca de capacidades y alcances del urgenciólogo, así como mejores relaciones entre los cirujanos de columna y los médicos de primer contacto podría ayudar a tener una adecuada referencia con el especialista en columna y ayudar a los pacientes independientemente de la patología. 7 La mayoría de los médicos de atención primaria se sienten «algo» preparados al comunicar el riesgo, así como para identificar los posibles casos de emergencia de la columna vertebral. La mayoría de los médicos de primer contacto refirieron que usan como fuente de información y conocimiento su entrenamiento realizado en la escuela de medicina y/o el realizado en la residencia médica al enfrentarse a emergencias de columna vertebral.…”
Section: Discussionunclassified
“…21 Finally, the last major surgeon factor affecting outcomes investigated in the literature is fellowship and specialty training. Despite studies showing different referral patterns, 22 complications and outcomes are reported to be similar between orthopedic and neurosurgery trained spine surgeons. A meta-analysis containing over 10,000 patients comparing outcomes between specialties only showed differences in incidence of wound complications and durotomies.…”
mentioning
confidence: 87%